2019
DOI: 10.1038/s41418-019-0389-3
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of FOXO3a by DNMT1 promotes breast cancer stem cell properties and tumorigenesis

Abstract: Breast cancer stem cells (BCSCs) are tumor initiating cells that can self-renew and are highly tumorigenic and chemoresistant. Therefore, the identification of factors critical for BCSC function is vital for the development of therapies. Here, we report that DNMT1-mediated FOXO3a promoter hypermethylation leads to downregulation of FOXO3a expression in breast cancer. FOXO3a is functionally related to the inhibition of FOXM1/SOX2 signaling and to the consequent suppression of BCSCs properties and tumorigenicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(81 citation statements)
references
References 62 publications
4
67
0
Order By: Relevance
“…We previously observed a negative correlation between FOXO3a expression and lymph node metastasis in breast cancer tissues (Supplementary Table 1 ) [ 25 ]. To determine the association between FOXO3a and tumor metastatic ability, we analyzed the protein expression of FOXO3a in several breast cancer cell lines.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously observed a negative correlation between FOXO3a expression and lymph node metastasis in breast cancer tissues (Supplementary Table 1 ) [ 25 ]. To determine the association between FOXO3a and tumor metastatic ability, we analyzed the protein expression of FOXO3a in several breast cancer cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…The loss of function of metastasis suppressor genes is a major rate-limiting step in breast cancer progression that prevents the formation of new colonies at distal sites [ 32 ]. Several lines of evidence demonstrated that downregulation of FOXO3a affects phenotypes such as cell proliferation, EMT, and stemness that contribute to breast cancer progression and poor response to therapies [ 10 , 25 , 33 , 34 ]. In the current study, our findings demonstrated that FOXO3a expression is inversely correlated with the migration ability of breast cancer cells and overexpression of FOXO3a suppresses breast cancer invasion and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Separately, FOXO3a is known to suppress breast cancer stem cells (BCSC) properties and tumorigenicity via inhibition of oncogenic FOXMI/SOX2 signaling. In this context, DNA methyl transferase (DNMT1)-mediated FOXO3a promoter hypermethylation leads to downregulation of FOXO3a expression in BCa, leading to the maintenance of BCSC population and associated with development of drug resistance [ 136 ]. Further, FOXO3a in collaboration with another TSG liver kinase B1 (LKB1) regulate CD44 expression and play a central role in CSC maintenance in pancreatic ductal adenocarcinoma [ 137 ]…”
Section: Foxo Familymentioning
confidence: 99%
“…Since our data showed that depletion of NIR enhanced FOXO3 expression while suppressing cell proliferation in MDA-MB231 cells, and FOXO3 has been shown to regulate cell growth. 19 We investigated whether NIR regulated cell proliferation via FOXO3 in breast cancer cells. Indeed, we observed that the enhanced proliferation of MDA-MB231 cells caused by overexpression of NIR can be reversed by ectopic FOXO3 expression ( Figure 9A and B ).…”
Section: Resultsmentioning
confidence: 99%